Table of Content - - (Journal of Curriculum and Teaching Methodology, 2025)
Table of Content: • Evaluating the performance of intermediate-level science teachers in Taif in light of some teaching competencies from their perspective Ms. Samar Safr Al-Harthi • Changes in the Arabic language curricula for the elementary stage in the city of Jerusalem in light of the policies of Israelization of education from the perspective of male and female teachers in private schools Ms. Safaa Khalil Abu Sharif • Content Analysis of Arabic Language Curricula in Saudi Arabia’s Elementary Stage in Light of Enhancing National Identity and Developing Skills Aligned with 21st-Century Requirements Dr. Abdullah Nasser Al-Yami • The Reality of Upper Primary School Students’ Use Of "Distance Learning" Tools During Crises from the Teachers’ Perspective in Al-Batuf Area – Palestine 1948 Ms. Haifa Mahmood Shehadeh • The role of the digital story in developing creative thinking among primary school students at Iksal C School Dr. Majeda Mazen Drawshy • The effectiveness of using interactive maps in teaching social studies to develop environmental awareness and visual thinking skills among tenth-grade students Mr. Mohammed Marzouq Dhafiyar Al-Ghafri • Serious creativity and smart applications in the educational process Mr. Ameer Hadi Obada